2021
DOI: 10.3350/cmh.2020.0227
|View full text |Cite
|
Sign up to set email alerts
|

Association between new-onset liver cirrhosis and suicide risk in South Korea: A nationwide cohort study

Abstract: Background/Aims: Current evidence suggests that liver cirrhosis (LC) causes severe psychological stress and depression, which are risk factors for suicide. Although previous studies reported the association between LC and suicidal thoughts, little is known of its effect on suicidal deaths. Therefore, this study was undertaken to investigate the effect of new-onset LC on suicide.Methods: From the National Health Insurance Service-National Sample Cohort of South Korea, 5,809 incident LC patients and 11,618 risk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Although the cohort was constructed retrospectively, this study was able to address many of the limitations inherent in a retrospective design through risk-set matching with time-dependent propensity score. 31 First, association between RA and risk of developing POAG was observed with time-dependent propensity score matching to adjust for confounders. 32 As with propensity score, we estimated hazard components from the Cox proportional hazard model, with January 1, 2004, as the baseline and RA as the event.…”
Section: Methodsmentioning
confidence: 99%
“…Although the cohort was constructed retrospectively, this study was able to address many of the limitations inherent in a retrospective design through risk-set matching with time-dependent propensity score. 31 First, association between RA and risk of developing POAG was observed with time-dependent propensity score matching to adjust for confounders. 32 As with propensity score, we estimated hazard components from the Cox proportional hazard model, with January 1, 2004, as the baseline and RA as the event.…”
Section: Methodsmentioning
confidence: 99%
“…The PD onset date was defined as the first hospitalization or second outpatient visit, whichever occurred first. The second outpatient visit was considered the date of PD diagnosis to avoid an immortal time bias [ 23 ], which is the interval between the first and second outpatient visits [ 24 ]. Thus, beginning on January 1, 2004, patients with new-onset PD were enrolled and followed up in the event PD cohort on the index date (i.e., time zero).…”
Section: Methodsmentioning
confidence: 99%
“…The National Health Insurance Service Senior–National Sample Cohort (NHIS-NSC) was constructed retrospectively, although this study was designed to mimic a prospective study. Therefore, here we solved many limitations inherent to retrospective design through risk-set matching with time-dependent propensity scores [ 23 , 25 ]. First, the association between PD and suicide risk was observed with time-dependent propensity score matching to adjust for confounding factors [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25,109,113,[270][271][272][273] A recent report found that patients with new cirrhosis diagnoses were at increased risk of suicide, highlighting the importance of identifying and treating mental health symptoms in this population. [274] Mental health symptoms can have organic causes (e.g., vitamin deficiency) and can mimic encephalopathy and dementia, such that a high index of suspicion is required to distinguish mental health symptoms from other related disorders.…”
Section: Depression and Anxietymentioning
confidence: 99%